Emerging technology and auditing practice : analysis for future directions - Thottoli, Mohammed Muneerali (2022)
Purpose – The purpose of this paper is to explore the effects of emerging technology (technology adoption, perceived benefits, technological challenges and ease of use) and the auditing practice of accounting professionals. Design/methodology/approach – The primary method of data collection was a questionnaire directed to newly practicing chartered accountants who are partners of sole proprietorship or partnership firms in India. The data were analyzed by using partial least squares structural equation modeling (PLS-SEM). Findings – The findings revealed that there is a positive and significant relationship between characteristics of emerging technology (technology adoption, technological challenges and ease of use) and auditing practice, while factors of the perceived benefits had a negative relationship with auditing practice. Research limitations/implications – The study model would aid technology enabled audit research by giving a platform for a new study to investigate further detailed solutions to emerging information technology determinants. Practical implications – This study illustrates how tools technique perceived benefit motivates sole proprietorship practicing auditors to adopt emerging technology- enabled auditing software for auditing client’s financial statements. Further, this study has added to the information technology auditing literature and might add benefits to the numerous other audit firms to adopt in emerging technology tools their audit firm. Social implications – Audit firms, generally sole proprietorship and partnership firms, should be given enough awareness about the latest audit software tools to carry out their audit tasks efficiently. Originality/value – The study findings highlight benefits of emerging technology-enabled auditing practice among owners/partners of the sole proprietorship or partnership firms, which is not extensively discussed in the prior studies. Furthermore, it broadens knowledge of perceived benefit, technological challenges and ease of use in technology-enabled audit software in the auditing and accounting literature.